Performing arts as educational methodology in higher education - Santiago Pérez-Aldeguer (FahrenHouse, 2017)
Over the last few years, the teaching and learning methodologies in higher education have undergone a great transformation, but there is still a long way if we want to meet the challenges of 21st Century society. A large number of these methodologies have influenced the higher education to a greater or lesser extent. After a process of creation, and/or recreation, terms such as «service learning», «cooperative learning» and «dialogic learning» have emerged. Step by step, we have become aware not only of the quality of the contents presented, but also of the educational methodologies applied. In this sense the performing arts have much to contribute.